Adverse Events Following COVISHIELD and VERO CELL Vaccination Campaigns Against COVID-19 - Adhikari, Santosh; Maharjan, Jessica; Bhattarai, Sushan; Kunwar, Kshitij; Agrawal, Sumit; Dangal, Raj Kumar; Chapagain, Ram Hari; Bista, Tek Bahadur; Bhattarai, Srijana (Journal of Nepal Health Research Council, 2024)
Background: Vaccination against COVID-19 for Nepalese was initiated in January 2021 for various age groups. People were anxious about receiving the vaccines and were concerned about the safety profile of the vaccine they received. In this study, we have tried to observe the Adverse Events Following Immunization of two different vaccines namely COVISHIELD (ChAdOx1 nCOV-19) and VERO CELL (CZ02 strain), used in different phases of vaccination by the government of Nepal. Methods: We conducted a cross-sectional study among people who received COVID-19 vaccines in this study using a self-administered questionnaire. Data was cleaned and then exported to IBM SPSS v.20 for analysis, Chi-square test was used to see the association between different variables and a p-value<0.05 was considered statistically significant. Results: Out of 303 respondents, all had received the first and 270 participants had received the second dose of the COVID-19 vaccine, among which, 133 (43.89%) reported at least one side effect after the first dose of vaccination while 58 (21.48%) had self-reported side effects after the second dose of vaccination. Seventeen percent of the respondents had COVID-19 infection within the past 3 months before receiving COVID-19 vaccine. Three percent of participants had re-infection with COVID-19 after receiving the first or the second dose of the COVID-19 vaccine. Among participants who experienced adverse events, 42% and 62.1% of participants experienced mild adverse events following the first dose and second dose of the vaccine, respectively. Conclusions: The adverse events following immunization for both vaccines after both doses of vaccination were quite low, with 43.89% of participants reporting side effects after the first dose and 21.48% of participants reporting side effects after the second dose. Adverse events were most frequently reported within 24 hours of vaccination and were mostly mild. There was no statistical significance of adverse events between both vaccines. Keywords: Adverse events following immunization (AEFI); COVID-19; COVISHIELD; VERO CELL.